(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This experience report to reflected on the construction of practices of counter-hegemonic academic production in the context of research experiences in a Public University. Anchored in the body and in the subjectivities of who writes and reads as a prerequisite to a sensitive writing, we analyzed experiences anchored in the concept of performative writing, relating it to the convocation of presence in the body by the artistic language of performance to produce (in)disciplines for a (de)education. By expanding the notion of writing, taking it as an experience articulated to other artistic materialities that may operate in a performative way, the text moved in search of what may become an academic writing.